Versatile Xenopus tropicalis model with targeted integration of human BRAF V600E - Rensen Ran; Lanxin Li; Peng Chen; Shuai Li; Peng Wang; Zhenpeng Zhu; Xiran Wang; Yonglong Chen; Jing Hang; Weizheng Liang (Proceedings of the National Academy of Sciences, 2025)
Targeting exogenous gene integrations in animals often exhibits low efficiency, limiting the development of gene knock-in models. Theoretically, by screening founder generation individuals based on the cell phenotypes resulting from gene knock-ins and leveraging the high fecundity of animals, heritable descendants with targeted knock-ins can be efficiently generated. Therefore, we utilized the high fecundity of Xenopus tropicalis and easily observable pigment phenotypes to construct a BRAF V600E -targeted mitf locus knock-in model. Results indicated that this approach enabled efficient generation of BRAF V600E knock-in X. tropicalis and produced a versatile frog model. The BRAF V600E knock-in induced the transdifferentiation of RPE cells into retinal cells, resulting in a symmetric retinal structure in the eyes of these frogs. The transformation of RPE cells ultimately leads to these frogs becoming eyeless frogs, which serve as a tool for retinal regeneration research. Additionally, in eyeless frogs the BRAF V600E knock-in led to the abnormal proliferation of both melanocytes and xanthophores into melanocytic and xanthocytic nevi respectively. Consequently, eyeless frogs provide a model for studying abnormal pigment cell proliferation, offering a platform for investigating pigment cell nevus formation. Furthermore, the cdkn2b -knockout eyeless frogs serve as a valuable xanthophoroma model for tumor biology research. Overall, the BRAF V600E -targeted knock-in X. tropicalis not only represents a strategy for constructing gene knock-in animal models but also serves as a versatile tool for research in retinal regeneration and tumor biology.